The Relationship between CC Ligand 5 Plasma Levels and Modic Changes in Low Back Pain Patients’ Severity - Firstisa Nuzulia Krinseani; Syarif Indra; Hendra Permana (HM Publisher, 2022)
Background: Low back pain (LBP) is one of the global health problems. The most common cause of LBP is disc degeneration. Modic changes (MC) are the most common MRI features in patients with disc degeneration. As a result of cartilage and disc tissue damage, CCL 5 is released and modulates pain responses in the dorsal root ganglion. This study aims to determine the relationship between CCL5 levels and the description of Modic changes on MRI with pain levels in patients with low back pain. Methods: This study is a cross-sectional study. The research subjects were LBP patients who were treated at the Neurology Polyclinic, Dr. M. Djamil General Hospital, Padang, in the range of March 2021-December 2021, who meets the inclusion and exclusion criteria. Subjects will be taken blood to assess CCL5 plasma levels, pain assessment using the McGill Pain Questionnaire, and undergo an MRI examination. Results: A total of 52 subjects consisted of 23 men and 29 women with an age range of 34-77 years. Most of the Modic changes were found in the type 2 group. Based on the pain scale, there were two groups with mild pain and moderate pain. On examination of plasma CCL 5 levels, the median value of plasma CCL5 levels was 303,271 ng/L. There was a significant relationship between plasma CCL5 levels and pain levels in patients with low back pain (p = 0.004). There was no significant relationship between Modic changes and the severity of pain. Conclusion: Plasma CCL5 levels are associated with pain levels in patients with low back pain, while Modic changes are not associated with pain severity.